“The show must go on”: tracks and mishaps of being a prostitute (Contextus - Revista Contemporânea de Economia e Gestão, 2018)
In its heyday, Guaicurus prostitution zone (Belo Horizonte, MG) was compared to other worldwide “renowned” ones, including the Parisian Moulin Rouge region. However, the women who work there, prostitutes, have always been stigmatized as targets of discrimination and violence. Thus, the purpose of this study was to analyze relations between the sense of work and the identity construction of prostitutes, by making a parallel with the film Moulin Rouge. For that, a qualitative exploratory research was operationalized through interviews based on thematic oral history with 17 prostitutes of that region; its data were submitted to discourse analysis (French approach). The analyses indicated fragile senses and fragmented, multifaceted identities. Daily suffering, silenced own pleasure and immature dreams portray that, whatever the cost, “the show must go on”.